QoS of Wi-Fi performance based on signal strength and channel for indoor campus network - Adiba Abd Ghafar; Murizah Kassim; Norsuzila Ya’acob; Roslina Mohamad; Ruhani Ab Rahman (Institute of Advanced Engineering and Science, 2020)
The implementation of Wi-Fi on campuses brings huge benefits for campus users in communications and education development. Some campuses face existing poor quality of service (QoS) on the Wi-Fi performance which is also unjustified and issues on unsatisfied connections. This research aims to analyses the Wi-Fi performance of the campus network for three indoor access points. Signal strength, usage percentage, channel utilization, and the number of clients count per access points are measured. Results show that 56% is the highest signal percentage and the lowest signal percentage is at 1%. Access point of Ustudent is the highest at 53% and lowest at 38%. The highest signal strength of -45dBm is found and the other two are below by -2 dBm. The lowest signal strength is at -95 dBm. SSID CCNA_1 is identified has the best signal strength compared to other SSIDs because it runs on 5 GHz frequency. The most channels used are channels 1, 4, and 6. Respectively 151, 67, and 57 users are connected to Ustudent, UHotspot, and CCNA_1. This study is significant for the QoS in a campus network in providing good network services. Thus, the QoS on Wi-Fi performance is improvised, monitored and analyzed for continues supports users in the campus network successfully.